1990
DOI: 10.1002/tox.2540050307
|View full text |Cite
|
Sign up to set email alerts
|

Development of a protozoan chemoattraction bioassay for evaluating toxicity of aquatic pollutants

Abstract: A microcapillary assay technique was developed to assess effects of pollutants on the chemoattraction of the ciliate, Tetruhyrnenu pyriformis. Parameters in the protocol such as starvation period, exposure period, and trough design were standardized in an effort to obtain consistent results.Cadmium, phenol, and naphthalene were tested for effects on ciliates' chemoattraction to 0.15% yeast extract. All three toxicants inhibited chemoattraction; cadmium had the greatest effect, followed by naphthalene and pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…This study demonstrates that murine fibroblasts, such as L-929, can be a successful substitute for the rodent laboratory models (such as rat or mouse) for screening study. Moreover, numerous studies have demonstrated that the protozoa T. pyriformis is also a convenient model for the toxicological evaluation of pharmaceutical drugs (Yoshioka and Ose, 1993), organic substances (Schultz et al, 1990;Yoshioka and Ose, 1993), inorganic substances (Bringhmann and Kuhn, 1980;Nilsson, 1989;Roberts and Berk, 1990), and water (Slabbert and Maree, 1986;Sauvant et al, 1994); thus, it has been proposed as the reference test system by the U.S. Environmental Protection Agency (Greenberg et al, 1992).…”
Section: Resultsmentioning
confidence: 98%
“…This study demonstrates that murine fibroblasts, such as L-929, can be a successful substitute for the rodent laboratory models (such as rat or mouse) for screening study. Moreover, numerous studies have demonstrated that the protozoa T. pyriformis is also a convenient model for the toxicological evaluation of pharmaceutical drugs (Yoshioka and Ose, 1993), organic substances (Schultz et al, 1990;Yoshioka and Ose, 1993), inorganic substances (Bringhmann and Kuhn, 1980;Nilsson, 1989;Roberts and Berk, 1990), and water (Slabbert and Maree, 1986;Sauvant et al, 1994); thus, it has been proposed as the reference test system by the U.S. Environmental Protection Agency (Greenberg et al, 1992).…”
Section: Resultsmentioning
confidence: 98%
“…With a pH of 6.5 to 7.0, its generation time is approximately 3 h, so the e!ects of pollutants on certain physiological and metabolic processes can be studied through several generations. Several test methods for xenobiotic toxicity using this ciliate have been proposed (Roberts and Berk, 1990;Noever et al, 1994;Sauvant et al, 1995;Bearden et al, 1997;Hegyesi and Csaba, 1997;Larsen et al, 1997). It has been acknowledged as an e$cient test organism for the detection of pollutant in aquatic ecosystems (Cronin et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…It has been acknowledged as an efficient test organism for the detection of pollutant in aquatic ecosystems (Cronin et al, 1991). Several test methods for xenobiotic toxicity using this ciliate have been proposed (Roberts and Berk, 1990;Noever et al, 1994;Sauvant et al, 1995;Larsen et al, 1997). Among the five ciliates tested in this study for copper uptake from the medium, RT-1 and T. thermophila showed greater efficiency than the others.…”
Section: Growth Of Tetrahymena Spp In the Presence Of Coppermentioning
confidence: 78%